Managing housing bubbles in regional economies under EMU: Ireland and Spain - Thomas Conefrey; John Fitz Gerald (The Economic and Social Research Institute (ESRI), 2009)
With the advent of EMU monetary policy can no longer be used to prevent housing market bubbles in regional economies such as Ireland or Spain. However, fiscal policy can and should be used to achieve the same effect. This paper shows that the advent of EMU relaxed existing financial constraints in Ireland and Spain, allowing a more rapid expansion of the housing stock in those countries to meet their specific demographic circumstances. However, the failure to prevent these booms turning into bubbles did lasting damage to the two economies, damage that could have been avoided by more appropriate fiscal policy action.
Keywords: 330; Eurozone; Immobilienmarkt; Immobilienpreis; Bubbles; Prognose; Irland; Spanien